2013
DOI: 10.1534/genetics.113.150110
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-Regulation Pathways During Egg Activation in Drosophila melanogaster

Abstract: Egg activation is the series of events that transition a mature oocyte to an egg capable of supporting embryogenesis. Increasing evidence points toward phosphorylation as a critical regulator of these events. We used Drosophila melanogaster to investigate the relationship between known egg activation genes and phosphorylation changes that occur upon egg activation. Using the phosphorylation states of four proteins-Giant Nuclei, Young Arrest, Spindly, and Vap-33-1-as molecular markers, we showed that the egg ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…The role of calcineurin in the activation process had previously been demonstrated only in the oocytes of the fly Drosophila (Krauchunas et al, 2013) and the frog Xenopus (Mochida and Hunt, 2007;Nishiyama et al, 2007), the involvement of calcineurin in the regulation of meiosis of these oocytes has also been confirmed. Our results indicate that calcineurin can regulate mammalian oocytes in the same way as it does in Drosophila and Xenopus oocytes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The role of calcineurin in the activation process had previously been demonstrated only in the oocytes of the fly Drosophila (Krauchunas et al, 2013) and the frog Xenopus (Mochida and Hunt, 2007;Nishiyama et al, 2007), the involvement of calcineurin in the regulation of meiosis of these oocytes has also been confirmed. Our results indicate that calcineurin can regulate mammalian oocytes in the same way as it does in Drosophila and Xenopus oocytes.…”
Section: Discussionmentioning
confidence: 94%
“…In oocytes, the role of calcineurin has been demonstrated during the regulation of meiotic maturation (Drosophila -Takeo et al, 2006 andpig -Petr et al, 2013). There is no information about calcineurin involvement in mammalian and porcine oocyte activation, even though the important role of this phosphatase has been demonstrated in Xenopus (Mochida and Hunt, 2007;Nishiyama et al, 2007) and Drosophila (Krauchunas et al, 2013) oocyte regulation, where it was confirmed that active calcineurin is necessary for oocyte exit from the second meiotic metaphase stage. Calcineurin phosphatase is responsible for the anaphasepromoting complex/cyclosome dephosphorylation and cyclin B degradation during oocyte activation (Mochida and Hunt, 2007;Nishiyama et al, 2007;Krauchunas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Egg activation also involves global changes in protein phosphorylation, and Cort is implicated in a subset of these [63]. One protein that is dephosphorylated at egg activation dependent on Cort is Gnu, a component of the Png complex that is implicated in translational control at egg activation [63].…”
Section: Egg Activation and The Resumption Of Meiosismentioning
confidence: 99%
“…Simon Lane (University of Southampton, Southampton, UK) presented measurements of APC/C activity by monitoring the degradation of cyclin B1 in mouse oocytes that undergo meiotic maturation. He observed that the timing of APC/C activation is dictated by the attachment of kinetochores to microtubules, but not by the alignment of bivalents on the metaphase plate nor by the tension on the kinetochores (Lane et al, 2012). He found that during meiosis, the initial attachment of chromosomes to kinetochores by microtubules partially activates the APC/C, independently of the biorientation status of the individual chromosomes.…”
Section: Spindle Assembly Checkpointmentioning
confidence: 99%
“…Using transcriptomic and proteomic approaches, they identified 4171 transcripts that become polyadenylated and 311 proteins that change their phosphorylation state during egg activation. Their work suggests that Sarah (calcipressin) and the Ca 2+ -activated phosphatase calcineurin are required for the APC/C-dependent degradation of Cortex (a meiosis-specific CDC20) upon egg activation (Krauchunas et al, 2013). Calcineurin was known to mediate release from metaphase II arrest in Xenopus (but not in mouse) eggs, but as Mariana Wolfner showed here, calcineurin probably mediates the release from metaphase I in Drosophila through its effects on the APC/C, suggesting a conserved role for calcineurin during egg activation.…”
Section: Egg Activationmentioning
confidence: 99%